Nil per os duration and anxiety: A single center cross-sectional study. (April 2023) - Klein, Elliot; Mauri, Juan; Lesserson, Linda-Shore; Nayyar, Pankaj
Abstract: Introduction: Preoperative fasting prior to general anesthesia or sedation is utilized to reduce the risk of aspiration and the severity of the pulmonary sequelae should aspiration occur. Consensus fasting guidelines are established, however, existing data indicates that patients continue to fast significantly longer than is recommended prior to surgery. The aim of this study was to understand the true preoperative solid and clear liquid fasting durations and its concomitant effect on somatic symptoms in patients undergoing surgery at a large tertiary care medical center. Methods: Ambulatory patients scheduled for elective procedures were enrolled during pre-surgical testing or on the day of surgery. Standard ASA fasting guideline base instructions were given to patients during their in-person pre-surgical testing visit. Subject participation required a brief in-person questionnaire prior to surgery. Patients were divided into morning, afternoon or evening groups and a one-way ANOVA was performed to compare mean fasting times. Results: Three-hundred-and-ninety-nine patients completed the survey. 95% (n = 379) of patients indicated that fasting instructions were clear prior to surgery; 4.76% (n = 19) recalled being told they could drink clear liquids up to two hours before surgery. Average fasting time for solids and clear liquids was 16.13 and 14.95 h. Mean solid fasting durations were 11.55, 15.03, and 17.73 h (p < 0.0001) and clear liquids fast durations were 10.00, 14.05, 16.80 h (p < 0.0001) for morning, afternoon and evening cases, respectively. Female patients and those reporting hunger and thirst preoperatively were more likely to report moderate to severe anxiety preoperatively (p = 0.007, p = 0.0002, p < 0.0001). Conclusion: Despite universal guidelines advocating for decreased fasting practices, nil per os times remain significantly prolonged. Preoperative anxiety is associated with prolonged solid and liquid fasting duration. Highlights: Preoperative fasting is a well-established modality for reducing the risk of perioperative aspiration. Universal guidelines recommend fasting times prior to elective surgery with longer fasting timer having adverse effects. Fasting times continue to remain significantly prolonged at many institutions. Prolonged fasting is associated with somatic symptoms such as anxiety in the preoperative period.